Underground sensing : monitoring and hazard detection for environment and infrastructure - Pamukcu, Sibel; Cheng, Liang (Academic Press, 2018)
Underground Sensing: Monitoring and Hazard Detection for Environment and Infrastructure brings the target audience the technical and practical knowledge of existing technologies of subsurface sensing and monitoring based on a classification of their functionality. In addition, the book introduces emerging technologies and applications of sensing for environmental and geo-hazards in subsurface - focusing on sensing platforms that can enable fully distributed global measurements. Finally, users will find a comprehensive exploration of the future of underground sensing that can meet demands for preemptive and sustainable response to underground hazards. New concepts and paradigms based on passively powered and/or on-demand activated, embeddable sensor platforms are presented to bridge the gap between real-time monitoring and global measurements.
Keywords: Underground utility lines -- Safety measures.; Underground construction -- Safety measures.; elektronické knihy; electronic books